34 trik kilat super sederhana menaklukan toefl + kunci sakti kuasai listening / Irham Ali Saifuddin & Bernando J.S. ; editor, Edi A.H. Iyubenu - IRHAM ALI SAIFUDDIN, 1977-; Bernando, J.S.; Edi A.H. Iyubenu (Saufa, 2014)
158 hlm. ; 20 cm + CD